Impact of capital Structure on Innovation and Performance of Small and Medium Enterprises in Nigeria: A study of the sector in the North Central States - Ilemona, Sani Alfred; Nwite, Sunday (Journal of Accounting Auditing and Business, 2024)
The issue of capital structure of Small and Medium Enterprises (SMEs) and the impact of each component on the innovation and performance of the sector in Nigeria has been lingering. A number of studies have been done on financial leverage businesses but none on SMEs in Nigeria. The aim of this study therefore is to examine the impact of capital structure on innovation and performance of SMEs in Nigeria: A study of the sector in the North Central States of the country. Random sampling technique was adopted and data were sourced primarily from 480 respondents comprising owners and managers of 127 SMEs operating in Plateau, Nasarawa, and Kogi States in the Central Zone of the country. Responses to the questionnaire designed to reflect five points Likert scale were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). Results indicated that Crowd Funding (CF) an external sources of finance has the most significant impact on the innovation and performance of these enterprises. The study recommended that while SMEs operators should develop a platform for exchange ideas on financing sources available to the sector, Enterprise Development Agency of Nigeria (SMEDAN), the regulatory authority of the sector in the country should develop programmes to encourage innovative ability of the operations of enterprises.